Production and Marketing System of Kampong Chicken in Batang Regency, Central Java, Indonesia - Agus Setiadi; Siswanto Imam Santoso; Suryani Nurfadillah; Kadhung Prayoga; Enggar Prasetyo (Caraka Tani: Journal of Sustainable Agriculture, 2020)
Kampong chicken is an indigenous chicken that gains popularity among consumers andit has good potentialsas a livestock commodity. But, the problem is most kampong chicken were kept in free range system without any standard of the rearing procedure and time. The farmers will sell their chickens by market’s requests. The study aims to determine the agribusiness production and marketing sub-system of kampong chickens. A hundred kampong chicken farmers from 9 sub-districts in Batang Regency were interviewed. Respondents were chosen by simple random sampling. Each farmer owned 4-120 kampong chickens with average number of 6.76 heads per farm. The poultry production sub-system consisted of six constituent variables, namely administration/bookkeeping, location, maintenance technology, maintenance system, business continuity and sanitation. Each constituent variable produced score of 1.44; 1.75; 1.68; 2.77; 1.55 and 2.03 respectively with the average value of 1.87. These results indicated that the applications of agribusiness production sub-systems were in the moderate category. The assessment of the marketing sub-system application included five variables namely marketing scale, marketing objectives, marketing technology, market information and pricing with the following scores 1.52, 1.76, 1.41, 1.85 and 1.18 respectively; or have an average value of 1.54. This result showed that the marketing sub-system has a moderate category. Improving the production system which consisted of the bookkeeping record, increase the number of rearing scale and sanitation process would improve farm productivity. Increasing marketing systems such as the application of electronic marketing would improve market efficiency. The results showed that the improvement of production and marketing agribusiness sub-systems are needed in order to increase farmers’ income.